Clinical Pharmacist Impact on Intensive Care Unit Delirium: Intervention and Monitoring. (June 2019) - Lightfoot, Myaa; Sanders, Adam; Burke, Christopher; Patton, Jessica
Purpose: The purpose of this study was to determine the impact of pharmacist monitoring with a clinical decision support system (CDSS) on clinical outcomes related to intensive care unit (ICU) delirium.Methods: This was a single-center, before-and-after study. This study compares patient outcomes of the preintervention group, which is the standard of care of pharmacist rounding, and the intervention group of pharmacy rounding with the CDSS rules. Using a CDSS, specific delirium risk factor rules were created to alert pharmacists to patients who have an increased risk of developing ICU delirium. Patients were included in the study if they were ⩾18 years of age, admitted to the trauma intensive care unit (TICU), and had one of the CDSS rule alerts. The CDSS notified pharmacists in real time to patients in the intervention group that met these criteria to provide timely recommendations in an effort to prevent ICU delirium.Results: Compared with the preintervention group receiving the standard of care (n = 28), the intervention CDSS group (n = 33) had a nonsignificant trend in decreased incidence of delirium (33.3% vs 24.1%, P = .45), ICU length of stay (LOS) (10.11 vs 7.55 days, P = .26), and ventilator duration (7.11 vs 5.03 days, P = .26). The intervention group had a significantly shorter hospital LOS (14.74 vs 9.98 days, P = .04). There was a nonsignificant increase in mortality with the intervention group from nondelirium causes (24.2% vs 7%, P = .07).Conclusion: The utilization of a CDSS by clinical pharmacists to monitor for delirium-specific risk factors led to a significantly shorter hospital LOS. Further studies using this model are warranted to see the impact on the ICU population.